Dialectical Behavior Therapy for Reducing Emotional Eating in Emerging Adult Women - Husodo, Chrissamary; Sukamto, Monique Elizabeth (Bulletin of Counseling and Psychotherapy, 2024)
Emerging adulthood is a transitional period from adolescence to adulthood characterized by instability in roles and relationships as individuals navigate the demands of higher education, employment, intimate relationships, and self-identity formation. This transition often triggers various negative emotions, such as anxiety, distress, and self-doubt, particularly in women, making them more susceptible to engaging in emotional eating as a means of seeking temporary comfort or distraction. Emotional eating is a mechanism for temporary emotional relief, but feelings of regret or guilt often follow it. Emotion regulation skills are crucial when experiencing negative emotions. This study aims to demonstrate the effectiveness of Dialectical Behavior Therapy (DBT), an intervention designed to enhance emotion regulation skills, in reducing the occurrence of emotional eating among emerging adult women. The study employed a single case experiment design with two 21-year-old female participants experiencing emotional eating. The Emotional Eating Scale (EES) and emotional eating self-recording were used as measurement tools. Each participant received DBT over 7 sessions, each lasting 60-90 minutes. The results indicated that DBT reduced the frequency of emotional eating in both participants, with the effect persisting up to 14 days post-intervention. These findings suggest that DBT is an effective intervention for reducing emotional eating in emerging adult women.